Β-Glucan, a dietary fiber in effective prevention of lifestyle diseases – An insight. (July 2019) - Maheshwari, Gunjan; Sowrirajan, Sumathi; Joseph, Baby
Abstract: β-Glucan (β-G), a dietary fiber and a biologically active natural polysaccharide, is helpful in the prevention and control of obesity, cardiovascular diseases, diabetics and cancer. Witnessing an increasing trend in mortality due to these diseases, especially in low- and middle-income countries can partly be attributed to dietary habits. This review deliberately discusses the global scenario on the life style diseases (LSDs), its relation to food habits on a regional basis and their effective prevention with β-glucan. Lowering the LDL cholesterol, the glycemic index and blood sugar, along with the antioxidant, anticancer and free radical scavenging property, β-glucan is efficient in trapping the reactive oxygen. But its easy availability as an affordable dietary supplement, is yet to be attended. Graphical abstract: Image 1